Informal Institutions and the State of Social Protection in Sub-Saharan Africa - Kpessa, M.W. (Sacha International Academic Journals, 2011)
This paper presents an institutional analysis of the social protection in sub-Saharan African countries and shows that because formal social security schemes in sub-Saharan African countries are limited in scope, informal institutional practices that derived their logic and legitimacy from familial and kinship relationships have become essential institutional rules that mediate interaction and social exchange in this issues area and beyond. This situation is exacerbated by the fact the recent institutional reforms such as structural adjustment and democratization in sub-Saharan Africa countries, but scholarly interest in the region prioritizes formal institutions without adequate attention to the role informal institutions play in shaping the incentive structures and choices of political actors and citizens. The paper also discusses the implications of the pervasiveness of informality in sub-Saharan African countries for broader socio-economic development and points to the need for greater attention to informal institutional analysis in the mainstream of comparative political analysis
Keywords: Governance; informality; institutions; reciprocity; social protection; Sub-Saharan Africa; nation-building